On the hodological criterion for homology - Faunes, Macarena; Francisco Botelho, Joao; Ahumada Galleguillos, Patricio; Mpodozis, Jorge (Frontiers in Neuroscience, 2015)
Owen’s pre-evolutionary definition of a homologue as “the same organ in different animals under every variety of form and function” and its redefinition after Darwin as “the same trait in different lineages due to common ancestry” entail the same heuristic problem: how to establish “sameness”. Although different criteria for homology often conflict, there is currently a generalized acceptance of gene expression as the best criterion. This gene-centered view of homology results from a reductionist and preformationist concept of living beings. Here, we adopt an alternative organismic-epigenetic viewpoint, and conceive living beings as systems whose identity is given by the dynamic interactions between their components at their multiple levels of composition. We posit that there cannot be an absolute homology criterion, and instead, homology should be inferred from comparisons at the levels and developmental stages where the delimitation of the compared trait lies. In this line, we argue that neural connectivity, i.e., the hodological criterion, should prevail in the determination of homologies between brain supra-cellular structures, such as the vertebrate pallium.